Two new feather mites of the genus Neocalcealges Orwig (Analgoidea: Trouessartiidae) from the Sichuan province of China - Wang, Zi-Ying; Proctor, Heather (Zootaxa, 2015)
Two new species of the feather mite genus Neocalcealges Orwig 1968 (Analgoidea: Trouessartiidae) are described from passerine birds (Passeriformes) from the Sichuan province of China: Neocalcealges davidi sp. nov. from Alcippe davidi Styan (Leiothrichidae) and N. chrysotis sp. nov. from Lioparus chrysotis (Blyth) (Paradoxornithidae). We provide a key to all described species of Neocalcealges.